Analysis of Social Factors on Immunization Refusal in Jungkat Village: Immunization Refusal - Andika, Andika; Rupita, Rupita; Marini, Marini; Bakri, Abu Rizal; Ramada, Triadi; Sabil, Ibnu; Kurniawan, Edi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Immunization is one of the most effective and efficient health intervention programs to prevent various diseases in children. But there are still refusals of immunization in some areas in West Kalimantan, one of which is in Jungkat Village. The low number of fully immunized children in Jungkat Village is a serious problem. As a result of not being immunized, dangerous diseases that can be prevented by immunization still threaten children in Jungkat Village. This study aims to understand and identify the factors of refusal of complete basic immunization in Jungkat Village, Mempawah District, West Kalimantan. Methods: This research used a descriptive qualitative approach.  The number of participants in this study was six people who were selected using purposive sampling method. Of the six people, consisted of the head of the Jungkat Health Center, posyandu officers, and three mothers who had toddlers aged 0-24 months. Results: Traditional beliefs and experiences: people in Jungkat village believe that bad things will happen after immunization, family support: without family support, mothers in Jungkat village will be less motivated to participate in the immunization program, parents. There are parents who do not understand why immunization is important for their children's health. Conclusions: Research on the factors of refusal of basic immunization in Jungkat Village, found that the factors of belief in tradition and community experience, community experience, family support, and parental knowledge greatly influenced community attitudes towards immunization.